The Effectiveness of Ict Media to Improve Students’ Activities and Science Learning Achievement at Fourth Grade (Journal of Primary Education, 2020)
This study aims to determine the effectiveness of ICT learning media The Heroes on students’ activities and learning achievement of fourth grade in SDN Tingkir Lor 02 Salatiga. The method was used Quasi Experimental Design with Control Group Pretest-Posttest type. Samples in this study were IVA and IVB class as a control class and an experiment class, respectively. Collecting data was used test to measure learning achievement and observation sheets for student activities during learning process. Data analysis was used independent t-test analysis, one-sample t-test, N-gain test, and simple linear regression using SPSS program. The observation sheets was analyzed using the checklist formula. Based on the analysis data shows the ICT media on the learning process is effective in the improving student activities and learning achievement. According to t-test analysis, experiment class has higher tvalue compare to the control class 0.41. Then, for the simple regression analysis has tvalue 0.848. The last, N-gain score of the experiment and control class was obtained 0.4 and 0.2, respectively, there are including low and medium criteria. Furthermore, due to the observation result, the observation sheet score on student’s activities was 20.4 with good criteria. The use of ICT media The Heroes has a significant effect on students’ activities as well as improving the learning achievement. The results of this study can be used to train students to find new knowledge, to improve their learning achievement, as well as to improve the quality of learning.